2002
DOI: 10.1149/1.1468647
|View full text |Cite
|
Sign up to set email alerts
|

A Photoelectrochemical Study of In[sub x]Ga[sub 1−x]N Films

Abstract: The III-nitride semiconductor n-In x Ga 1Ϫx N was investigated by optical absorbance and luminescence measurements and by various photoelectrochemical methods. Evidence is found for the presence of localized states and compositional fluctuations. Upon illumination with the appropriate wavelength and positive polarization in an indifferent electrolyte, i.e., aqueous 1 mol L Ϫ1 HCl, photocurrent flow is observed, resulting in the photoanodic etching of the solid. Measurements of the quantum efficiency Q and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…The top-down approach involves the plasma etching of patterned epitaxially-grown InGaN/GaN wafers. Almost all studies, irrespective of growth method, are focused on improving the PEC performance of InGaN/GaN photoanodes by incorporating higher In concentrations into either planar [25][26][27][28][29] or nanostructured [11,12,[17][18][19][20][21][22][23] devices. As a consequence, there are no reports on the comparative studies of the influence of In concentration on PEC performance of InGaN/GaN MQWs in planar and NP photoanodes.…”
Section: Introductionmentioning
confidence: 99%
“…The top-down approach involves the plasma etching of patterned epitaxially-grown InGaN/GaN wafers. Almost all studies, irrespective of growth method, are focused on improving the PEC performance of InGaN/GaN photoanodes by incorporating higher In concentrations into either planar [25][26][27][28][29] or nanostructured [11,12,[17][18][19][20][21][22][23] devices. As a consequence, there are no reports on the comparative studies of the influence of In concentration on PEC performance of InGaN/GaN MQWs in planar and NP photoanodes.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, single crystalline In x Ga 1-x N nanowires with compositions up to x = 0.4~0.5 have been realized. 16 Although the InGaN alloy is a very promising water splitting material, only a few studies have been reported [17][18][19] with no studies on nanowire geometries.One dimensional nanostructures have been demonstrated to be efficient in photoelectrochemical (PEC) cell and photovoltaic cell applications because they can decouple the directions of light absorption and charge carrier collection. [20][21] When the life time of the minority carrier is short, the minority carrier can recombine in bulk before it reaches the semiconductor/electrolyte junction.…”
mentioning
confidence: 99%
“…1-3 Ultraviolet light accounts for only about 4% of the solar spectrum, while visible light is about 43%. 10,11,13 In this study, we used alternative electrolytes to prevent the photoetching of In x Ga 1−x N electrode. 4-8 III-V nitrides have suitable band gaps to utilize solar energy.…”
mentioning
confidence: 99%